Area-wide augmentation of Anagyrus vladimiri and Cryptolaemus montrouzieri enhances biological control of mealybugs in Lambrusco vineyards in Northern Italy - Giovanni Burgio; Serena Magagnoli; Roberto Mondini; Emilio Guerrieri; Luca Casoli; Marco Profeta; Sabina Capponcelli; Alessandro Castiglioni; Stefano Meglioraldi; Matteo Mora; Stefania Valeriani; Martina Parrilli (Biological Control)
An area-wide augmentative biological control program against vineyard mealybugs was conducted in a Lambrusco vineyard cultivation area in the Emilia-Romagna region (Northern Italy), releasing the parasitoid Anagyrus vladimiri and the predator Cryptolaemus montrouzieri. A sampling program was established to evaluate the biological control efficacy of these natural enemies, within 16 pilot farms, following the principles of the Integrated Pest Management adopted in the region. The effectiveness of the natural enemies was evaluated by comparing the situation before and after 3 years of releases. Results showed that the dominant mealybug was Pseudococcus comstocki (75 % in 2019 and 86 % in 2022), followed by Planococcus ficus. A significant increase in parasitism rate and predator density was recorded in release farms compared to the control ones, with the parasitism rate reaching a median value of about 80 %. Mealybug infestation patterns, and to some extent the activity of natural enemies, showed some variability among the farms monitored. A positive correlation between A. vladimiri and C. mountrouzieri biocontrol activity revealed a lack of competition between them. The increase of insecticide treatments in release farms did not result in a higher efficacy of control, but negatively affected the parasitism rate. In conclusion, augmentative biological control promoted the activity of natural enemies, likely enhancing the dispersal of parasitoids. Our results highlight the need to combine a biological control strategy with an Integrated Pest Management approach based on the reduction of insecticide sprays, the use of more selective active ingredients, and the proper timing of treatments.